INTANGIBLE CULTURE RELATED TO AGRICULTURAL TRADITIONS (EXAMPLE OF FERGANA VALLEY) (Scientific journal of the Fergana State University, 2025)
This article discusses intangible cultural heritage related to economic traditions. In the lifestyle of the people of Ferghana Valley, there are customs, ceremonies and holidays related to ancient philosophical, religious, calendrical concepts and economic traditions. Community life embodies various traditions. They have been inherited from ancestors to generations for centuries. These customs and ceremonies can be divided into such groups as calendar, labor, family and religious. These ancient traditions, incorporating new aspects, have been living in the lifestyle of our people until now.